Quantitative Assessment of Liver Stiffness Using Ultrasound Shear Wave Elastography in Patients With Chronic Graft‐Versus‐Host Disease After Allogeneic Hematopoietic Stem Cell Transplantation: A Pilot Study. (23rd October 2018) - Zhang, Man; Mendiratta‐Lala, Mishal; Maturen, Katherine E.; Wasnik, Ashish P.; Wang, Sherry S.; Assad, Hadeel; Rubin, Jonathan M.
Abstract : Objectives: The purpose of this study was to compare hepatic stiffness on ultrasound (US) shear wave elastography (SWE) in patients with chronic graft‐versus‐host disease (GVHD) after allogeneic hematopoietic stem cell transplantation versus patients with no underlying liver disease. Methods: We performed a retrospective analysis of 4901 patients who underwent abdominal US examinations with adjunctive liver SWE between August 2014 and December 2016. Each patient was scanned supine with gentle breath holding on LOGIQ E9 (GE Healthcare, Waukesha, WI) or Epiq (Philips Healthcare, Andover, MA) US machines (3–6 MHz). Three to 10 measurements were made intercostally in the right hepatic lobe, following manufacturers' guidelines before release of the 2015 Society of Radiologists in Ultrasound consensus or the 2015 Society of Radiologists in Ultrasound consensus. The median and standard deviation of the shear wave velocity (SWV) were obtained. A 2‐sample t test with the Welch approximation was used for statistical analysis. Results: Six patients had documented hepatic chronic GVHD or a high clinical suspicion of liver chronic GVHD. All had normal pretransplant liver function test results and no pretransplant or posttransplant hepatic infection. The control group, obtained from the same database, contained 10 patients with normal liver function test results, no abdominal pain, and no history of liver disease or conditions that may have caused liver stiffness changes. The SWVs in patients with chronic GVHD were double those in the control group (1.96 ± 0.28 versus 0.98 ± 0.27 m/s; P < .0001). Conclusions: Patients with chronic GVHD had substantially higher hepatic parenchymal SWVs than patients without liver disease, indicating increased tissue stiffness. To our knowledge, this phenomenon has not been previously reported in chronic GVHD and suggests potential utility of SWE for diagnosis and monitoring of disease progression and the treatment response in this cohort of patients.